2020
DOI: 10.1186/s12903-020-01333-x
|View full text |Cite
|
Sign up to set email alerts
|

Familial oral lichen planus in a 3-year-old boy: a case report with eight years of follow-up

Abstract: Background Oral lichen planus (OLP) is a chronic mucocutaneous disease characterized by adult predominance and a prolonged course. However, it is rare in the pediatric population with familial aggregation. Case presentation A 3-year-old boy presented with pain and irritation on the oral mucosa while contacting spicy food for 2 months. Oral examination showed widespread whitish reticular and papular lesions on the lips, the dorsum of the tongue, and bilateral buccal mucosa, with diffuse erosions covered with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In addition, basal cell layer degeneration was detected in all samples of the present study, which was severe in most CLP cases but moderate in the majority of OLP lesions. In many studies, including the current research, basal cell degeneration was observed in 100% of samples [7,11,12,16,25]. However, low amounts were reported in some studies, including the research by Rampal (81.7%) [18] In a research by Chatterjee et al, which was performed on OLP lesions of subjects below the age of 18, basal cell layer degeneration was observed in all samples, which was moderate and mild in 63.64% and 36.36% of the cases, respectively [26] .…”
Section: Discussionmentioning
confidence: 51%
“…In addition, basal cell layer degeneration was detected in all samples of the present study, which was severe in most CLP cases but moderate in the majority of OLP lesions. In many studies, including the current research, basal cell degeneration was observed in 100% of samples [7,11,12,16,25]. However, low amounts were reported in some studies, including the research by Rampal (81.7%) [18] In a research by Chatterjee et al, which was performed on OLP lesions of subjects below the age of 18, basal cell layer degeneration was observed in all samples, which was moderate and mild in 63.64% and 36.36% of the cases, respectively [26] .…”
Section: Discussionmentioning
confidence: 51%
“…While the incidence of familial LP reportedly varies from 1% to 11% of all LP patients (Bermejo‐Fenoll & Lopez‐Jornet, 2006), familial OLP is even less common (Lu et al., 2016). Between 1970 and 2020 there were publications on less than 50 families with familial LP, some with oral involvement [17–20], (Bermejo‐Fenoll & Lopez‐Jornet, 2006; Lu et al., 2016: Singal, 2005; Wang et al., 2020). In the current study we describe 20 families with familial OLP.…”
Section: Discussionmentioning
confidence: 99%
“…Although a pediatric OLP population has been reported [13], familial cases are very rare. OLP predominantly affects adults, especially women after the fourth decade of life [14].…”
Section: Etiology and Initiation Of Olpmentioning
confidence: 99%